Volume 3: Pipeline and Riser Technology; Ocean Space Utilization 2008
DOI: 10.1115/omae2008-57365
|View full text |Cite
|
Sign up to set email alerts
|

Steel Catenary Riser Design Based on Coupled Analysis Methodology

Abstract: In a riser design, the traditionally assessment adopted by industry for attainment of platform motions applied to the top of riser consists in the use of de-coupled methodologies. These formulations consider the static environmental loads over the platform (current and wind) through a static offset and the dynamic environmental loads due to wave through imposition of top riser displacement calculated from cross spectral response of sea spectrum and vessel’s RAOs (Response Amplitude Operators). Nowadays due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Those results are important to explain the difference between the offset obtained for the analyses performed in DEEPC and MIMOSA submitted to the extreme loading cases presented in [3]. Figures 7 and 8 show the comparative results for the vertical motions of the SCR top obtained from coupled and decoupled analyses when that riser was submitted to the same environmental loads.…”
Section: Figure 6 -Lines Restoring Force For South and West Directionmentioning
confidence: 76%
See 2 more Smart Citations
“…Those results are important to explain the difference between the offset obtained for the analyses performed in DEEPC and MIMOSA submitted to the extreme loading cases presented in [3]. Figures 7 and 8 show the comparative results for the vertical motions of the SCR top obtained from coupled and decoupled analyses when that riser was submitted to the same environmental loads.…”
Section: Figure 6 -Lines Restoring Force For South and West Directionmentioning
confidence: 76%
“…It could be observed that the system considering all lines in DEEPC presents horizontal stiffness significantly higher than the one obtained from MIMOSA with mooring lines only, which resulted in smaller static offsets as shown in Figures 5 and 6. Other studies considering the same offshore floating system submitted to the extreme environmental loads are presented in [3]. • System Restoring Comparison: Important conclusions are also obtained with the comparison between the system restoring comparison of coupled model (DEEPC), considering all lines (riser + mooring) connected and the platform model without any lines connected.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In the equation (1) [6], A as the thermal conductivity of materials(w/m.k), q as heat flux(w/m 2 ) , T x -T 2 as the temperature difference between solid surfaces( °C ), q as physical distance between two surfaces (m), as the temperature gradient between surfaces.By the formula (1) , obtained: q = h(T l -T 2 )ld ■> known as A = 20.93 (tool material) [7], T X = 350 °C , T 2 = 20 °C , d = 0.03m > heat flux can be calculated as, q = 0.23w / mm 1 .…”
Section: Static Analysis Of Various Other Overhang Of the Toolmentioning
confidence: 99%